Comparison of outcomes between axillary and femoral artery cannulation for type A aortic dissection surgery - ZhenHong Wang; YiHui Yu; XinYi Xie; LinLin Wan; Lei Wang; JiaLin Yin (Journal of Cardiothoracic Surgery)
Abstract Objective To compare the application and outcomes of femoral versus axillary arterial cannulation in adult patients undergoing surgery for type A aortic dissection. Methods We conducted a retrospective review of 108 patients who underwent surgery for type A aortic dissection, dividing them into two groups based on the type of arterial cannulation utilized: the femoral artery cannulation group (n = 53) and the axillary artery cannulation group (n = 55). We assessed their general condition, cardiopulmonary bypass time, and the occurrence of major postoperative complications. Multivariate logistic regression models were used to identify independent predictors of mortality risk factors. Results The operative mortality rates were comparable between the two groups, with axillary cannulation at 18.1% and femoral cannulation at 15.1%. Multivariate logistic analysis identified age (70 years or older) and prolonged extracorporeal cardiopulmonary bypass time (250 min or more) as independent risk factors for surgical mortality. The rates of early stroke, renal injury, and cognitive dysfunction were similar in both groups. Conclusion The findings indicate that femoral and axillary arterial cannulation yield similar outcomes in patients with acute type A aortic dissection. The choice of cannulation site should be individualized based on each patient’s specific risk factors. Additionally, preoperative hemodynamic instability, the duration of cardiopulmonary bypass (CPB), and a high body mass index (BMI ≥ 30 kg/m²) are independent predictors of operative mortality.